Stop Bulliying: Sosialisasi dan Penyuluhan Upaya Pencegahan Perundungan di Sekolah Dasar Negri Kranggan 1 Kota Mojokerto Dengan Pendidikan Karakter - Muhaimin, Hikmah; Wijaya, Dian; Afandi, Ahmad Hasan; Santosa, Santosa; Lailiyah, Fatihatul; Angggi, Clarissa (Fakultas Ilmu Sosial dan ilmu Politik, 2025)
The problem of bullying among students at school is very worrying because it is recurrent and is even considered to be just a joke, which can disturb the victim's psychological well-being. Bullying behaviour can occur in various environments with various types of bullying being committed. Verbal and relational bullying behaviour in school environments is often perceived by students as a joke or they may not even realise that these two actions constitute bullying. Greater awareness of bullying, as well as more positive anti-bullying attitudes and behaviours, Bullying behaviour is aggressive and manipulative and can cause conflict for both the perpetrator and the victim. One of the causes is a lack of understanding of bullying among students, as well as a lack of understanding of character education. The objective of this community service activity is to educate students about bullying by promoting anti-bullying behaviour, in order to increase students' knowledge about bullying behaviour. The material was delivered using PowerPoint and evaluated through direct questions and answers during the presentation. The methods used in this activity included lectures, questions and answers, discussions, demonstrations and mentoring. The results achieved in this activity are students' understanding of the negative impacts of bullying behaviour. Participants in the activity are aware of their respective responsibilities in preventing bullying behaviour in the school environment. This activity is able to foster self-control to develop good habits in the family, school, and community environments.